Evaluation of sexual dimorphism in maxillary and mandibular canine using mesiodistal, labiolingual dimensions, and crown height - Neelakshi Pandey; Mang Shin Ma (Wolters Kluwer Medknow Publications, 2016)
Context: Gender estimation is one of the most important parameters in forensic identification. Teeth being the central component of the masticatory apparatus of the skull is a good source of material for civil and medico-legal purpose. Gender estimation using dental features is primarily based on the comparison of tooth dimensions in male and female. Aims: To analyze the presence of sexual dimorphism in maxillary and mandibular canine using mesiodistal (MD), labiolingual (LL), and height of crown. Subjects and Methods: A total number of 100 subjects (50 males and 50 females) were included in the study between the age group of 20 and 25 years. Dimensions (MD, LL, height of crown) of maxillary and mandibular canine were recorded with a digital vernier calliper. Statistical Analysis Used: The data obtained is subjected to statistical analysis using Student's t-test and intra-reliability test. Results: The present study revealed that male shows larger mean dimensions of teeth than female. Out of all the four canines, right maxillary canine shows highly consistent results for sexual dimorphism. Hence, by drawing the conclusion, it can be stated that right maxillary canine can be used as an adjunct along with other procedures for gender estimation. Conclusion: The findings support the usefulness of employing odontometric analysis of the canine teeth in gender estimation. It is an easy, reproducible, and objective method.